Mediastinoscopic salvage esophagectomy for recurrent esophageal squamous cell carcinoma after definitive chemoradiotherapy in a previously pneumonectomized patient. Issue 4 (8th November 2018) - Okumura, Tomoyuki; Seto, Yasuyuki; Aikou, Susumu; Moriyama, Makoto; Sekine, Shinich; Hashimoto, Isaya; Shibuya, Kazuto; Hojo, Shozo; Yoshioka, Isaku; Nagata, Takuya; Fujii, Tsutomu
Abstract: We herein report a case of mediastinoscopic salvage esophagectomy for recurrent esophageal squamous cell carcinoma after definitive chemoradiotherapy in a previously pneumonectomized patient. A 66‐year‐old man with a medical history of left‐sided pneumonectomy for lung cancer was diagnosed with local recurrence of lower esophageal squamous cell carcinoma (cT3N0M0 cStage II) 9 years after definitive chemoradiotherapy. The mediastinoscopic cervical approach and laparoscopic transhiatal approach were combined, and the thoracic esophagus was safely mobilized to separate the esophagus from the stump of the left bronchus and to divide dense adhesions between the esophagus and fibrotic tissue at the site of the previous left mediastinal pleural resection. The esophagectomy was uneventful and followed by reconstruction with a gastric conduit via the retrosternal route. The pathological diagnosis was esophageal squamous cell carcinoma (pT3‐AD, pN1, M0, pStage III), indicating R0 resection. Even as salvage surgery, mediastinoscopic esophagectomy is a safe and curative treatment strategy for esophageal cancer patients who have previously undergone pneumonectomy.